Distinct patterns of association between the hemoglobin glycation index, the stress–hyperglycemia ratio, and the risk of new-onset atrial fibrillation in critically ill patients - Jie, Qiqiang; Li, Gang; Qian, Weichun; He, Mingzhu; Jia, Haibo; Zhang, Fengfu; Wang, Jianping (Frontiers in Endocrinology, 2025)
BackgroundThis study investigated the associations between two novel glycemic indices, the hemoglobin glycation index (HGI) and the stress hyperglycemia ratio (SHR), and the risk of new-onset atrial fibrillation (NOAF) in critically ill patients.MethodsWe retrospectively analyzed data from 3,882 adults in the MIMIC-IV database, with the primary outcome defined as NOAF within 7 days of intensive care unit (ICU) admission. Multivariate Cox regression and restricted cubic spline analyses were used to evaluate associations.ResultsNOAF occurred in 750 patients (19.3%). After adjustment for confounders, HGI exhibited a significant inverted U-shaped association with NOAF risk, with the highest risk in intermediate quartiles. In contrast, the SHR demonstrated a significant linear inverse relationship with NOAF risk, with higher SHR quartiles consistently associated with lower risk. These associations were especially pronounced in nondiabetic patients and remained consistent across key clinical subgroups.ConclusionOur findings indicate that the HGI and SHR independently predict NOAF in critically ill patients and may provide valuable tools for risk stratification and personalized glycemic management in the ICU.